Recognition and screening for Chagas disease in the USA - Rachel Marcus; Andrés F. Henao-Martínez; Melissa Nolan; Elizabeth Livingston; Stephen A. Klotz; Robert H. Gilman; Monica Miranda-Schaeubinger; Sheba Meymandi (Therapeutic Advances in Infectious Disease, 2021)
Chagas disease (CD), caused by the protozoan Trypanosoma cruzi , is a public health concern, mainly among countries in South and Central America. However, despite the large number of immigrants from endemic countries living in the USA, awareness of CD is poor in the medical community, and therefore it is significantly underdiagnosed. To avoid the catastrophic cardiac complications of CD and to prevent maternal–fetal transmission, widespread educational programs highlighting the need for diagnosis are urgently needed.